PHONOLOGICAL INTERFERENCE IN JAVANESE LANGUAGE OF BANYUMAS DIALECT IN FAMILY DOMAIN IN PURWOKERTO - Andika, Yunilis; Sumarlam, Sumarlam; Abdullah, Wakit (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The objective of this research is to identify the type of phonological interference in Javanese Language of Banyumas dialect in family domain in Purwokerto and also its factor. As the administrative center of Banyumas regency, the researcher selects Purwokerto especially in Northern Purwokerto, Southern Purwokerto, Eastern Purwokerto, and Western Purwokerto as the location of data collection. The research is descriptive qualitative research which was conducted by sociolinguistic study. The instrument used to collect the data is the uninvolved conversation observation technique, recording technique, notation technique, questionnaire and in-depth interview. The method used to analyze the data is identifying method combined with appeal correlation technique. The result of this research shows that there is phonological interference in Purwokerto society, there are phonemic vowel and phonemic consonance, although the phonemic semivowel isn’t found in this research. The interference existed derive from Indonesian and English languages which interfere Javanese language of Banyumas dialect. The factor of the habit becomes the factor of the interference manifestation. Interference manifestation as the process of being interfered in the Javanese language structure of dialect Banyumas make an ambiguity in the using of language, in that case interference should be avoided or even should disappear. However, interference has a positive side. The phenomenon of language interference in conversation is used by speaker to support communication activity because it can cover lingual unity in that Javanese languages of Banyumas dialect don’t have.